QUANTIFYING GREENHOUSE GAS EMISSIONS FROM CORPORATE OFFICE OPERATIONS: PT PLN (PERSERO) UNIT INDUK DISTRIBUSI (UID) KALSELTENG CASE STUDY - Novieta Rosianasari; Muralia Hustim; Sumarni Hamid Aly; Hardianti Alimuddin; Fauziatul Husna (Universitas Trisakti, 2025)
Office-based operations in the energy sector are an underrecognized yet significant source of greenhouse gas (GHG) emissions. At PT PLN (Persero) UID Kalselteng-the main electricity provider for South and Central Kalimantan-routine administrative and technical activities contribute to emissions primarily through electricity consumption, fossil fuel vehicle use, and solid waste generation. Aim: This study aims to identify and quantify the main emission sources from PLN’s office operations over a three-year period (2022-2024), and to propose actionable mitigation strategies aligned with PLN’s decarbonization targets and Indonesia’s national sustainability goals. Methodology and results: Using the 2006 IPCC Guidelines, emissions were calculated across three categories: electricity use, transportation fuel, and waste disposal. The analysis shows that electricity consumption is the dominant source, contributing an average of 6,447.56 tons CO₂-eq per year (83% of total emissions). This is followed by emissions from operational vehicles at 1,175.30 tons CO₂-eq (15.2%) and solid waste at 107.85 tons CO₂-eq (1.4%). Conclusion, significance and impact: These findings reveal that office-level emissions-particularly in energy utilities-are both substantial and symptomatic of broader structural inefficiencies in emission control. Addressing these is critical for advancing sustainability, as they significantly impact organizational carbon footprints. Accordingly, this study recommends four key mitigation strategies: (1) retrofitting offices with energy-efficient systems, (2) transitioning to electric vehicles, (3) implementing zero-waste-to-landfill policies, and (4) initiating localized tree-planting programs for carbon offsetting. Together, these measures support integrated sustainability efforts by reducing emissions, improving resource efficiency, and reinforcing PLN’s leadership in sustainable public utility operations across Indonesia and Southeast Asia.